Get Involved: Everglades Restoration - Alyssa Dodd; Mark A. Brennan (EDIS)
FCS-9260, a 3-page fact sheet by Alyssa Dodd and Mark Brennan, offers information and ideas to Florida residents and visitors who would like to learn about or become involved in the ongoing restoration of the Everglades. Published by the UF Department of Family, Youth and Community Sciences, July 2007.